I need help finding the inverse of f(x)=7^3x-5 with work shown.

your f(x)=7^3x-5 is ambiguous

did you mean it the way your typed it or
f(x)=7^(3x-5)

The way you typed it:

let y = 7^3x - 5
y + 5 = 7^(3x) , another ambiguity, the way you typed it, it would be
(7^3)(x)
I will go with my last interpretation.

y + 5 = 7^(3x)
step 1 is to interchange the x and y variables , so we get
x + 5 = 7^(3y)
step 2 is to solve this new equation for y, this requires logs

log(x+5) = log ( 7^(3x) )
log(x+5) = 3x(log7)
x = log(x+5)/(3log7) , x > 5

if you meant y = 7^(3x-5)
then we get x = 7^(3y-5), and now take logs of that etc.

jgip87opgpy8iu

To find the inverse of a function, f(x), we need to interchange the x and y variables and solve for y.

Given f(x) = 7^(3x-5), let's start by interchanging the x and y variables:

x = 7^(3y - 5)

Next, we solve for y. To do this, we need to isolate the exponential term:

7^(3y - 5) = x

Taking the logarithm of both sides of the equation will help us isolate the exponent:

log base 7 (7^(3y - 5)) = log base 7 (x)

Using the logarithm property, we can bring the exponent to the front:

(3y - 5) log base 7 (7) = log base 7 (x)

Since log base 7 (7) equals 1, the equation simplifies to:

3y - 5 = log base 7(x)

Now, isolate the y variable by adding 5 to both sides of the equation:

3y - 5 + 5 = log base 7(x) + 5

3y = log base 7(x) + 5

Finally, divide both sides of the equation by 3 to solve for y:

(3y)/3 = (log base 7(x) + 5)/3

y = (1/3) * (log base 7(x) + 5)

So, the inverse function of f(x) = 7^(3x-5) is:
f^(-1)(x) = (1/3) * (log base 7(x) + 5)

To find the inverse of a function, a common approach is to switch the x and y variables and then solve for y.

Step 1: Replace f(x) with y:
y = 7^(3x) - 5

Step 2: Swap the x and y variables:
x = 7^(3y) - 5

Step 3: Solve the equation for y.

Let's go through the steps to find the inverse:

Step 1: Add 5 to both sides of the equation to isolate the exponential term:
x + 5 = 7^(3y)

Step 2: Take the logarithm (log base 7) of both sides to eliminate the exponential term:
log₇(x + 5) = 3y

Step 3: Divide both sides by 3 to solve for y:
y = (1/3) * log₇(x + 5)

Therefore, the inverse of f(x) = 7^(3x) - 5 is:
f^(-1) (x) = (1/3) * log₇ (x + 5)

Please note that in order for the inverse function to be well-defined, certain restrictions may apply in terms of the domain and range of the original function.